2004
DOI: 10.1001/archotol.130.4.465
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Cauterization of Fourth Branchial Cleft Sinus Tracts

Abstract: To evaluate the effectiveness of endoscopic cauterization as definitive treatment for fourth branchial cleft sinuses. Design: Retrospective chart review with follow-up questionnaire. Setting: Tertiary care children's hospital. Patients: Ten children (age range, 10 months to 10 years) with fourth branchial cleft sinuses treated with endoscopic cauterization between 1995 and 2002. Main Outcome Measure: Recurrence of neck infections after endoscopic cauterization of fourth brachial cleft sinus tracts. Results: Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 9 publications
3
58
2
7
Order By: Relevance
“…4 However, a 2008 literature review found 526 published cases of PFST, 5-fold more than previously thought to exist. 5 Many more cases have been reported since then, although PFST prevalence has varied in reports from a number of individual institutions.…”
mentioning
confidence: 99%
“…4 However, a 2008 literature review found 526 published cases of PFST, 5-fold more than previously thought to exist. 5 Many more cases have been reported since then, although PFST prevalence has varied in reports from a number of individual institutions.…”
mentioning
confidence: 99%
“…Por estas razones, se recomienda realizar una laringoscopía directa ante la sospecha de una anomalía de cuarto arco branquial 21 . Se describe también que al realizar la maniobra de valsalva durante una tomografía computarizada o un esofagograma con bario, podría ayudar a abrir el trayecto sinusal tornándose éste más visible 22,23 . Además queremos destacar la utilidad del estudio con nasolaringofibroscopía en nuestra serie, mediante el cual fue posible observar edema del seno piriforme comprometido en dos de los casos, lo que orientó aún más la sospecha diagnóstica.…”
Section: Discussionunclassified
“…Por otro lado, la resección quirúrgica de la lesión branquial, particularmente cuando se ha asociado a tiroidectomía parcial ha presentado tasas de recurrencia significativamente menores, sin embargo, este manejo presenta mayores tasas de complicaciones particularmente en menores de 8 años 13 . El tratamiento endoscópico, reportado en 62 casos 13 , representa una técnica mínimamente invasiva en la cual se cauteriza y oblitera la apertura del trayecto fistuloso en el seno piriforme 13,23 . Esta técnica ha demostrado tasas de recurrencia similares respecto a cirugía abierta de cuello y resección de la lesión, con menores tasas de complicaciones y menor costo 13 .…”
Section: Discussionunclassified
“…12 Endoscopic cauterization of the fourth branchial cleft sinus has been reported with effective result compared with open excision. 13 Treatment by chemocauterization of the internal opening with trichloroacetic acid (TCA) has been reported with encouraging results. 2,14 In 2009, Nixon and Healey reported the role of sclerotherapy for treatment of branchial sinus tract.…”
Section: Discussionmentioning
confidence: 99%